ISOLASI KITIN, KARAKTERISASI, DAN SINTESIS KITOSAN DARI KULIT UDANG - Sry Agustina; I Made Dira Swantara; I Nyoman Suartha (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
Chitosan is the modification of chitin which found on the outer skin of Crustacea species such as shrimps and crabs. This study aims to isolate chitin, syntesize and charactetize chitosan from shrimp shells. Chitin isolation stage included demineralization using HCL 1.5M and deproteination step with NaOH 3.5%. Transformation of chitin into chitosan was done through the deacetylation reaction by using NaOH 60%. The result showed that characteristic of the chitosan obtained in this research was as follows: the yield of transformation chitin into chitosan was 67.08%; it had a white color powder texture with had no smell; water content 1.55%; It solubled in 2 % acetic acid with 84.85 % deacetylation.